HASAN AL-BANNA AL-IKHWAN AL-MUSLIMUN - Musyarif, Musyarif (LPPM IAIN Parepare, 2017)
This article examines the thoughts of Hasan Al Bann, founder of the Ikhwan alMuslimun movement. The method used in examining the results of Al Banna’s thought is the literature review through books or literature related to the object being studied or supporting documents such as journals and related articles. This paper uses text studies using a hermeneutic paradigm to interpret the character of Hasan have thought. The results of the study show that Al-Ikhwan al-Muslimin was formed as a medium of the struggle of Hasan al-Banna with his friends in launching da’wah messages. Hasan al-Banna’s concept and movement is the spirit of jihad secured to all aspects of life on the basis of faith.